2008
DOI: 10.1002/pmic.200700784
|View full text |Cite
|
Sign up to set email alerts
|

Aorta protein networks in marginal and acute zinc deficiency

Abstract: Human zinc deficiency is a global problem and may influence the development of cardiovascular disease. Our objective was to determine Zn deficiency affected pathways and protein interactions in rat aorta and their likely influence on stress-induced atherogenesis. In two separate studies, rats were given diets acutely (<1 mg Zn/kg) or marginally (6 mg Zn/kg) deficient in Zn. Both studies included Zn adequate controls (35 mg Zn/kg) and the acute deficiency study included a pair-fed group. After 6 wk, proteins fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…In zinc deficiency a diverse range of symptoms is reported, including growth retardation, impaired immunity and endocrine dysfunction . Genomic analysis suggests a link between zinc and chronic diseases, and zinc deficiency is reported to contribute significantly to the global burden of disease . Although severe zinc deficiency is relatively rare in developed countries, based on population estimates of dietary zinc intake, mild deficiency states are believed to be highly prevalent …”
Section: Introductionmentioning
confidence: 99%
“…In zinc deficiency a diverse range of symptoms is reported, including growth retardation, impaired immunity and endocrine dysfunction . Genomic analysis suggests a link between zinc and chronic diseases, and zinc deficiency is reported to contribute significantly to the global burden of disease . Although severe zinc deficiency is relatively rare in developed countries, based on population estimates of dietary zinc intake, mild deficiency states are believed to be highly prevalent …”
Section: Introductionmentioning
confidence: 99%
“…[9] Zinc deficiency has been implicated in hyperglycemia, [10] diabetes, [11] and cardiovascular disease. [12] Furthermore, we previously reported that early micronutrient deficiency (zinc and iron) was linked to later cognitive deficit [13] and increased externalizing behavior outcomes in children. [14] …”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a humoral factor which mediates the response of tissues to lowered zinc status may provide a mechanism to understand how reduced dietary zinc intake can influence arterial protein expression (22) and accelerate the development of atherosclerotic plaque in a mouse model of atherosclerosis (14). In the present microarray study, pathway analysis of the 1600 significantly regulated genes ( P <0.001), which were 2‐3‐fold changed by ZD9 compared to PF27 (therefore, excluding all highly regulated genes), showed a dominance of pathways related to apoptosis and survival, cytoskeletal remodeling, cell adhesion, and cell cycle (44% of the top 50 pathways).…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently noted that dietary zinc deficiency modulates the levels of some aortic proteins related to the phenotype of vascular smooth muscle cells (VSMCs) in rats (22) and that a marginally ZD status increases the development of aortic atherosclerotic plaque in a mouse model of atherosclerosis (14). In the rat studies (22), plasma zinc was unaffected by mild zinc deficiency, and yet changes in the levels of many aortic proteins were detected using proteomic methodology. We hypothesized that a zinc‐sensitive humoral factor may be mediating the effects of zinc deficiency, and so we designed a series of cell culture studies, using primary rat VSMCs, to test the presence of such a factor.…”
mentioning
confidence: 99%